Economic integration and sowing life in San Miguel de las Palmas - González-Espinosa, Ana Mercedes; Garza-Bueno, Laura Elena; Caamal-Cauich, Ignacio; Matus-Gardea, Jaime Arturo Matus-Gardea; Almeraya-Quintero, Silvia Xóchilt (Revista Mexicana de Ciencias Agrícolas, 2026)
The sowing life program has benefited thousands of producers from several states in the country through monthly monetary support in exchange for planting certain crops. Such is the case in the state of Guerrero, where producers decided to plant mezcalero maguey, leading to a considerable increase in production; consequently, they are now looking for ways to market it. One of the communities interested has been San Miguel de las Palmas. Throughout 2023 and 2024, an impact research work was conducted in parallel with a training process for producers; through these activities, three alternatives for marketing agave were analyzed: selling maguey hearts, transforming the hearts into mezcal individually or producing and packaging mezcal collectively. After examining these options, it was detected that the only profitable option was to create a company that produces, packages and markets mezcal, under the producers’ own management. By homogenizing processes and managing with quality standards, they will be able to market mezcal at a price of 400.00 L-1, making producers achieve greater profits. These results ensure that producers obtain income similar to that provided by the sowing life program, which is expected to support new producers and new territories.